2006
DOI: 10.1007/s00210-006-0104-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three radioligands for the labelling of human β-adrenoceptor subtypes

Abstract: We have compared the ability of three radioligands, [(125)I]-cyanopindolol, [(3)H]-CGP 12,177 and [(3)H]-dihydroalprenolol, to label the three human beta-adrenoceptor subtypes. Saturation and competition binding experiments were performed using membrane preparations from Chinese hamster ovary cells stably transfected with the three subtypes. While [(3)H]-CGP 12,177 had very similar affinity for beta(1)- and beta(2)-adrenoceptors (about 40 pM), [(125)I]-cyanopindolol and [(3)H]-dihydroalprenolol had 4- to 6-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 30 publications
0
44
0
Order By: Relevance
“…(Baker 2005;Hoffmann et al 2004;Niclauß et al 2006;Tate et al 1991). While [ 3 H]-dihydroalprenolol has been proposed to label β 3 -adrenoceptors in porcine lower urinary tract tissues (Yamanishi et al 2002a,b), a systematic comparison of its binding to all three cloned human subtypes found only very poor labeling of β 3 -adrenoceptors (Niclauß et al 2006). This is entirely consistent with the low β 3 -adrenoceptor affinity of unlabeled alprenolol (Hoffmann et al 2004 (Roberts et al 1993).…”
Section: Detection Of β 3 -Adrenoceptorsmentioning
confidence: 76%
See 3 more Smart Citations
“…(Baker 2005;Hoffmann et al 2004;Niclauß et al 2006;Tate et al 1991). While [ 3 H]-dihydroalprenolol has been proposed to label β 3 -adrenoceptors in porcine lower urinary tract tissues (Yamanishi et al 2002a,b), a systematic comparison of its binding to all three cloned human subtypes found only very poor labeling of β 3 -adrenoceptors (Niclauß et al 2006). This is entirely consistent with the low β 3 -adrenoceptor affinity of unlabeled alprenolol (Hoffmann et al 2004 (Roberts et al 1993).…”
Section: Detection Of β 3 -Adrenoceptorsmentioning
confidence: 76%
“…Subsequently, it has been used in numerous studies in which inhibition of a functional response by this compound has been taken as evidence for mediation of this response by a β 3 -adrenoceptor (Sarma et al 2003;Yamanishi et al 2002bYamanishi et al , 2003. However, more recent radioligand binding studies with cloned human β-adrenoceptor subtypes have reported that SR 59,230 is not selective for β 3 -adrenoceptors and, if anything, has slightly lower affinity for this subtype than for β 1 -and β 2 -adrenoceptors (Table 2) (Candelore et al 1999;Hoffmann et al 2004;Niclauß et al 2006). Moreover, SR 59,230 can exhibit agonist rather than antagonist properties and, in some systems, even behave as a full agonist (Horinouchi and Koike 2001;Hutchinson et al 2005).…”
Section: Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…In isolated human bladder, KUC-7322 was slightly less potent than in the monkey bladder and much less potent than in the rat bladder in two independent studies performed against either passive tension of KCl-induced tone but remained a full agonist relative to isoprenaline . The response against KClinduced tone was not affected by the β 1 -adrenoceptor antagonist CGP 20,712A or the β 2 -adrenoceptor antagonist ICI 118,551,but surprisingly also not by the general β-adrenoceptor antagonist SR 59,230A (Niclauß et al 2006). In contrast to the other agonists, bladder relaxation by solabegron has not been reported in rats as the primary animal species but has been in dogs (Hicks et al 2007).…”
Section: Isolated Tissue Studiesmentioning
confidence: 91%